Desain Pembelajaran Jarak Jauh Berbasis E-Learning pada Pelajaran Fisika SMA - Martini Martini; Ismet Ismet; Ketang Wiyono (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
The background of this research is the existence of globalization which makes education very important for all people. One way to significantly expand access to education is through distance learning (PJJ). PJJ can provide comfort for students to study independently anywhere and anytime. The implementation of PJJ has been widely carried out using LMS (Learning Management System). The purpose of this research is to produce a distance learning design based on e-learning on valid and practical temperature and heat material. This research uses mix method research with ADDIE development model. There are two subjects in this study, namely learning design in google classroom and students of class XI MIPA 1 SMA Negeri 15 Palembang, totaling 36 students. Instruments in this study were validation and practicality sheets and interviews. The results of the media and material validation questionnaire analysis as well as the media practicality questionnaire in the study obtained an average media validation score of 3.67 or 91.75%, the average material validation score obtained 3.31 or 82.75% and practicality questionnaire analysis got 3.13 or 78.07% , this shows that these media and materials are feasible and practical to use.